Extracellular vesicles derived from different sources play various roles in diabetic retinopathy - Chen, Tingting; Wang, Fang; Wei, Jiayi; Feng, Le (Frontiers in Endocrinology, 2023)
Extracellular vesicles (EVs) are present in almost all biological fluids and secreted by almost all cell types. A growing number of studies have revealed the potential roles of EVs in the diagnosis and treatment of the diabetic retinopathy (DR). Changes in the quantity and content of EVs may serve as biomarkers of cause or consequence of pathological status of DR, such as inflammation, neovascularization and epithelial-mesenchymal transition. In addition, as natural, safe and efficient drug carrier, EVs have been reported to play important roles in intercellular communication by acting for essential cell-specific information to target cells. In this review, we summarize the roles of EVs, secreted by various types of cells and participated in various biological processes, in the pathogenesis, diagnosis, and treatment of DR.